Physico-Chemical Characterization Of Maluku Nutmeg Oil - Ilyas Marzuki; Bintoro Joefrie; Sandra A. Aziz; Herdhata Agusta; Memen Surahman (International Journal of Science and Engineering, 2014)
The essential oil of Banda nutmeg was extracted using hydro-distillation method to characterize their essential oil and volatile components.  Banda, Ambon, and Luhu nutmegs were chosen as sample ecotypes. Nutmeg oils were subjected to physico-chemical and GC-MC analyses.  Results indicated that nutmeg from the three ecotypes produced uncolored oils with the contents in mature seed were 11.69, 11.92, and 9.99%, respectively. Meanwhile those of immature seeds contained 13.32, 11.99, and 11.03% respectively.  Furthermore, the physico-chemical of the oil are specific gravity 0.897 to 0.909 g/ml; refraction index, 1.489 to 1.491; and optical rotation, +11.40 to +16,30.GC-MS analysis suggested that essential oils Maluku nutmegs composed of 28 to 31 components and also showed that nutmeg from Banda comprised 52.8% monoterpene hydrocarbon (MH), 21.11% oxygenated monoterpene (OM), and 18,04% aromatic compound (AC); Ambon’s 45.12% MH, 24.51% OM, and 16.97% AC; and Luhu’s 56.06% MH, 27.34% OM, and 13.62% AC.  Further analysis indicated that there were four important volatile oils fractions in nutmegs i.e. myristicin, elemicin, safrole, and eugenol. Maluku nutmeg contain 5.57 to 13.76% myristicin and 0.97 to 2.46% safrole. In conclusion, nutmeg oil shows a high stability in all physico-chemical properties.  Nutmeg from Banda ecotype has the highest content in myristicin.